Evaluation of alternate wetting and drying irrigation technique on rice production under Malaysia rice soils / Nurafiqah Mohd Rosli - Mohd Rosli, Nurafiqah (Faculty of Plantation and Agrotechnology, 2018)
Freshwater demands have been projected to increase significantly in the coming decades due to population growth, urbanization, and economic development. Therefore, rice industry could face huge problem due to high water usage. Alternative methods to plant rice with reduced water need to be established to sustain rice production. Research was conducted at the Greenhouse UiTM Jasin to find out possible effects of Alternate Wetting and Drying (AWD) as a water saving irrigation on the yield, growth, water productivity and weed incidence after water reduction. During this experiment five treatments of water management were compared; 5cm continuous flooding; AWD at 5cm below soil surface, flooded during flowering; AWD at 5cm below soil surface, even during flowering; AWD at 10cm below soil surface, flooded during flowering; and AWD at 10cm below soil surface, even during flowering. From this study, rice grain yield, height and SPAD did not significantly differ among the five treatments. The application of AWD did not affect the growth and yield of paddy. However, amount of total water use was significantly reduced by AWD, indicating that AWD is an effective technique to increase water productivity. However, this AWD technique also has side effects of weed increase significantly. Therefore, when applying AWD in rice cultivation, weed management should be done efficiently.